Epidemiology of Human Toxoplasmosis at Erbil Governorate /Kurdistan Region / Iraq - salih, Mustafa Khalid; Ayyed Taha, Mustafa Riyadh; Azzawi Jassim, Abdul Sattar Khalil; Mohammed, Amara Hameed Jassim (American Journal of Biology and Natural Sciences, 2024)
Human toxoplasmosis is a worldwide significant food-borne zoonotic disease that results from the infection with T. gondii ,(Toxoplasma gondii)which is a ubiquitous, single-celled, obligate intracellular protozoan parasite of warm-blooded vertebrates, including humans, land and sea mammals, and various bird species. The aim of the present study was to analyses the diagnostic yield of the Latex and Biozek techniques for the rapid diagnosis of human toxoplasmosis in Erbil Governorate. The research project included 120 human blood samples. Latex and Biozek were positive for 25/120 (20.8%) individuals with toxoplasmosis, The infection in female was higher 15/59(25.4%), while the rate of infection in male was lower 10/61(16.4%). After analysing the models and made the statistics of the most age infected individuals with the disease are those aged between 31-40 years (36.7%), also we confirmed that the frequency of infection with this disease in urban and rural areas were (21.3%) and ( 20.0%). Regarding the rate of infection during the period of study, we noticed that in November 15/62 (24.2%), then in December 5/26 (19.2%), while the lowest rate was found in February 1/11(9.1%). We concluded that the prevalence of T.gondii among human in Erbil Governorate was high, and the infection occurred at different stages of life. The significance of public health hazards was discussed.